Yoga Asanas as an Effort to Reduce Anxiety on Online Learning During Pandemic in Stikes Buleleng Students - Putu Agus Windu Yasa Bukian; I Wayan Sujana (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
The impact of the COVID-19 pandemic has attacked many sectors, including the education sector, which requires students to take part in online learning. This learning requires students to do assignments and achievements in accordance with the profile of graduates coupled with the unfinished pandemic situation causing students to experience more anxiety, this requires complementary therapies, one of which is yoga. This study aims to see differences in anxiety levels in the control group and the group given the yoga asanas treatment. The research method used is the pre-posttest design. Where the samples were taken were 23 control groups and 23 treatment groups. Control and treatment respondents were given a questionnaire first, then the control group was given IEC to reduce anxiety, while the treatment group was given yoga asanas which were carried out for 3 weeks. Furthermore, a posttest was given to assess the differences in the respondents' anxiety levels. The results showed that there were differences in the level of anxiety before and after in the control group (p-value 0.16) and the treatment group (p-value 0.001). Then the results of the different test analyses showed that there was a difference in the level of anxiety between the control group and the group given yoga asanas (p-value 0.01). The conclusion is that there are effective yoga asanas to reduce anxiety levels in students who take online learning during the pandemic.